Gender equality and the cultural economy: comparative perspectives - Anheier, Helmut K.; Markovic, Darinka; Todd-Tombini, Sofia (Routledge Taylor & Francis Group, 2025)
"The status of women in the creative and cultural industries remains precarious in comparison with men. This comparative analysis provides insights from seven key economies to help understand progress toward gender equality in culture and the arts and the broader cultural economy. With empirical and policy analysis of France, Germany, Italy, Poland, Sweden, the United Kingdom and the United States, the authors investigate the extent to which gender equality has entered the mainstream, using two phenomena as the organizing trope: the Lost Frida Kahlos Problem, i.e., loss of female talent due to structural barriers, and the Bauhaus Women Problem, i.e., the structural forgetting of women who managed to gain access. The authors assess gender equality along five dimensions: leadership (the extent to which women advance to leadership positions in the cultural economy); access (equal access to training and career opportunities); gaps (pay, pension, old-age poverty risk); balance (support systems that allow for reconciliation of work and family life); and monitoring (tools measuring gender equality in the cultural economy). This book is essential reading for scholars, policymakers, and reflective practitioners across the human and social sciences, especially those involved with arts management and the creative industries more broadly."
Includes bibliographical references and index
Keywords: Geschlechterverhältnis; Kulturindustrie